Case report: Anxiety and depression as initial symptoms in a patient with acute hypoxia and patent foramen ovale - Zhai, Xiaoyan; Jiao, Ronghong; Ni, Aihua; Wang, Xueyi (Frontiers in Psychiatry, 2023)
The prevalence of patent foramen ovale (PFO) is 15-35% among adults. The role of right-to-left shunting through the PFO, anxiety, depression, and hypoxemia in systemic remains poorly understood. Herein, we present a case of a 52-year-old female with no heart and lung disease admitted due to anxiety for five months and symptoms exacerbation with dizziness for four days presenting with cyanosis. She was noted to have acute hypoxemia, with an oxygen saturation of 94.48% on room air, and arterial blood gas showed an oxygen tension of 65.64 mmHg. Agitated saline contrast echocardiography showed right-to-left shunting due to PFO. Arteriovenous fistula, pneumonia, pulmonary embolism, pulmonary hypertension, congestion peripheral cyanosis, ischemic peripheral cyanosis, and methemoglobin were excluded. Additionally, the patient improved by taking Paroxetine, Oxazepam, and Olanzapine. Her oxygen tension returned to 90.42 mmHg, and her symptoms resolved. In case of severe anxiety and depression, right-to-left shunting through the PFO may cause acute systemic hypoxemia via a flow-driven mechanism, occasionally manifesting as cyanosis. When anxiety improved, hypoxia also improved. Thus, the treatment of anxiety and depression seems effective in improving hypoxemia. Notably, this is a rare report, and we hope to draw the attention of psychosomatic specialists, psychiatrists, and clinicians to seek the relationship between anxiety appearing as acute stress and PFO. This may be a new therapeutic method for treating severe anxiety disorder.